PENGEMBANGAN MODUL PRAKTIKUM UNTUK MODULATOR OPTIK INTERNAL DAN EKSTERNAL - Nurulita Aini; Pande Ketut Sudiarta; Nyoman Putra Sastra (Jurnal SPEKTRUM, 2021)
The optical modulator is a component used to convert information signals into a carrier signal in theform of a light beam. 3 optical modulators are widely used, namely the internal modulator, the machzehndermodulator (MZM), and the electro-absorption modulator (EAM). Each optical modulator hasadvantages and disadvantages, but in general, the purpose of an optical modulator is to modulatelight beams. The purpose of this study was to determine the performance comparison of the internaland external optical modulator and the feasibility of the practicum module. The method used is tosimulate an optical modulator on a fiber-optic network using Optisystem software. The networkfeasibility parameters analyzed were Q-factor, BER, and eye diagram until performance reached theITU-T G.984.2 standard with a minimum limit of Q-factor = 6 and BER 10-9. The optical modulatorchanges internal and external variables. The feasibility test of the practicum module uses the methodof filling out a questionnaire with a Likert scale of 1–5 and giving pre-test and post-test to thepractitioner. The comparison of optical modulator performance shows that MZM performance is betterthan EAM and internal modulator. In the bit rate test, the transmission distance used is 65 km, andsignal power of +7 dBm MZM is capable of sending bit rates of up to 27 Gbps. In testing thetransmission distance, the bit rate used is 10 Gbps, and signal power of +7 dBm MZM can cover adistance of up to 70 km. In the signal power test, the bit rate used is 10 Gbps and the transmissiondistance is 65 km MZM capable of working at +5 dBm signal power. This practicum module is veryfeasible as teaching material according to the percentage of the practitioner's assessment of 88.2%.